Mild liquid phase oxidation of benzyl alcohol in the presence of microporous framework copper silicates - Neves, Patrícia (2022)
The microporous framework copper silicates CuSH-1NaK (1) and SGU-29 (2) – prepared using hydrothermal conditions – are effective heterogeneous oxidation catalysts for producing benzaldehyde (BzAld) and benzoic acid (BzAcid) from benzyl alcohol (BzOH), under mild reaction conditions (approxi-mately atmospheric pressure, 70 °C). The copper silicate heterogeneous catalysts triggered a radical reaction mechanism leading to the target products; in particular, BzAcid was formed in up to 94 % yield and 100 % selectivity from BzAld. The type of oxidant and solvent influenced the catalytic performances.